Analysis of Factors Causing Traffic congestion on Kasokandel Highway, Majalengka - Moch Yoga Purnama Rifa’i; Muhamad Taufik; Mulia Pamadi (LEADER: Civil Engineering and Architecture Journal, 2025)
Road traffic congestion on highways has become the most important concern in various countries in the present era. Congestion has become one of the most common problems in densely populated cities due to the rapid growth of transportation use. Road users need traffic signs for information, warnings, and regulations, to reduce road accidents. The purpose of writing this journal is to investigate problems related to traffic congestion to determine urbanization and infrastructure development, this congestion problem is discussed in the journal. The location of this research was carried out on the highway kasokandel, district Kasokandel, district Majalengka, West java. In this qualitative research, we will examine a very complex congestion problem, involving various causal factors and involving many interested parties. Traffic congestion is a major challenge for heavily populated cities, especially in industrialized areas with high population density. Traffic signal systems, signs, traffic regulations are to regulate traffic for safety and efficiency. In the planning of Development of transportation infrastructure and its impact on traffic flow is very important to overcome the problems of traffic congestion, activity Point in time delays, and impacts on the surrounding environment. A highway is a public road built to connect regions, cities, or areas with each other and is used by two- Plus more-wheeled vehicles. Road users need traffic signs for information, warnings, and regulations, to reduce road accidents. Roadways have facilities for pedestrians such as sidewalks, crosswalks, and roadside paths are very important components for pedestrians in the surrounding environment Pedestrian. Therefore, the results of this study are needed to improve infrastructure, road design, and reduce the use of high-emission transportation.